Hubungan antara Iklim Kelas dengan Motivasi Belajar Siswa Sekolah Dasar - Gamilina, Pranciska (FONDATIA, 2024)
This research aims to obtain the description of classroom climate and student learning motivation, as well as examining the relationship between classroom climate and students learning motivation at SDN Sungai Raya 1. This research uses a quantitative approach. The population is 18 class IV students. The sampling technique used a total sampling technique. The data collection technique used was an indirect communication technique using a questionnaire. Determining the correlation between classroom climate and learning motivation using correlation calculations between variables. The results of the research that has been carried out can be concluded that based on the statements of students at SDN Sungai Raya 1, most students stated that the classroom climate was in the very good category with a percentage of 39%, followed by the good category at 33%, then the moderate category at 22%, and the least is in the less category at 6%. Meanwhile, students' learning motivation at SDN Sungai Raya 1 is mostly in the high category with a percentage of 38%, followed by the very high learning motivation category at 28%, then the moderate learning motivation category at 22%, and the least is the low motivation category at 11%. Data from research on classroom climate with learning motivation which was calculated using the correlation formula between variables with the help of SPSS version 20, the results were rcount 0.691 > rtable 0.468, this result shows that there is a significant relationship between classroom climate and student learning motivation at SDN Sungai Raya 1.